DIRECTORS DIVERSITY, BUSINESS STRATEGY, SALES GROWTH ON TAX AVOIDANCE - Delina Herdian Septiani; Toni Heryana; Nugraha Nugraha (Universitas Pendidikan Indonesia, 2022)
The Covid-19 pandemic has affected the growth of world trade, including Indonesia. The decreases in the Indonesian economy has made the performance of tax revenue has not been optimally. This study aims to analyze the effect of directors diversity, business strategy, sales growth on tax avoidance. This study is a descriptive and verification study with a quantitative approach. This study used all companies that are included in the healthcare sector and the telecommunications sector listed on the IDX as population. The sample in this study amounted to 80 companies with secondary data obtained from the IDX website and their respective company websites consisting of annual reports and financial statements for 2018-2021. The data analysis technique used is the PLS-SEM path equation model with SmartPLS 3.2.8. The results of the study found that: 1) the directors diversity have an effect on tax avoidance, while sales growth and business strategy have no effect on tax avoidance; 2) the directors diversity have an effect on business strategy; 3) business strategy and directors diversity have an effect on sales growth; 5) directors diversity have an effect on sales growth through business strategy; 6) directors diversity have not effect on tax avoidance through business strategy; 7) business strategy have not effect on tax avoidance through sales growth. This study has limitations in data, but compared to other studies, the results of this study are more updated and carried out in two different sectors than previous studies.